Water determines the products: an unexpected Brønsted acid-catalyzed PO–R cleavage of P(iii) esters selectively producing P(O)–H and P(O)–R compounds. Issue 11 (14th May 2019) - Li, Chunya; Wang, Qi; Zhang, Jian-Qiu; Ye, Jingjing; Xie, Ju; Xu, Qing; Han, Li-Biao
Abstract : Water is unexpectedly found to determine a TfOH-catalyzed C–O cleavage reaction of trialkyl phosphites to produce H-phosphonates or alkylphosphonates selectively. Abstract : Water is found able to determine the selectivity of Brønsted acid-catalyzed C–O cleavage reactions of trialkyl phosphites: with water, the reaction quickly takes place at room temperature to afford quantitative yields of H-phosphonates; without water, the reaction selectively affords alkylphosphonates in high yields, providing a novel halide-free alternative to the famous Michaelis–Arbuzov reaction. This method is general as it can be readily extended to phosphonites and phosphinites and a large scale reaction with much lower loading of the catalyst, enabling a simple, efficient, and practical preparation of the corresponding organophosphorus compounds. Experimental findings in control reactions and substrate extension as well as preliminary theoretical calculation of the possible transition states all suggest that the monomolecular mechanism is preferred.